AN APPROACH TO ELEMENTARY ACCOUNTING FOR NON-BUSINESS STUDENTS. - Perry, Richard S. (The Accounting Review, 1959)
Three movements among colleges and universities now threaten the lives of all lower-division courses in business administration. The first is the return to an undergraduate program dominated by the liberal arts courses; the second, complementing the first, is the postponement of all professional education until the upper-division or preferably the graduate years; the third is the elimination of all courses which are "pre-judged" as occupational and vocational in objective. Elementary accounting, the foundation course for practically all curricula in business administration, appears to be directly in the path of these three movements. If it is to survive the onslaught, it may have to undergo some drastic revisions. The author of this investigation examined rather closely the objectives of the elementary accounting course and compared these objectives with the needs of the students who take either one or both semesters of the course. The findings indicate that a large proportion of college students who enroll in the usual elementary course, especially those who take only the first semester course, would benefit more from a one-semester course in which emphasis is placed on the understanding of financial data and the fundamentals of corporate accounting.